Evaluasi Proteksi Sabun Kalsium Sebagai Pakan Suplemen Berdasarkan Kecernaan Bahan Kering, Kecernaan Bahan Organik dan pH In Vitro di dalam Rumen dan Pasca Rumen - A., Pramono; Kustono, Kustono; Widayati, D. T.; Putro, P. P.; Handayanta, E.; Hartadi, H. (Universitas Sebelas Maret (UNS), 2013)
The research aims to evaluate calsium soap protection as feed supplement based on dry matterdigestibility, organic matter digestibility and pH in vitro in the rumen and post rumen. Calsium soapwas produced from sardine fish oil and soybean meal, through two protection methods. It wassaponification and microencapsulation. This research used Split Subject Repeated MeasurementDesign with 3 treatments (calcium soap, soybean meal and pangola grass) which each treatment wasrepeated 5 times. The observation kinetics of dry matter digestibility, organic matter digestibility, andpH rumen fluid were done in incubation times (2, 4, 8, 12, 24 and 48 hours respectively). The firstresults of the research showed that in the first step (rumen) has dry matter digestibility of calciumsoaps: 38.65; 40.00; 42.66; 46.32; 54.40 and 51.40% respectively; organic matter digestibility: 39.44;41.27; 44, 31; 46.32; 56.62 and 52.50% respectively. Kinetics of pH rumen fluid: 6.89; 6.79; 6.78;6.74; 6.71, and 6.88 respectively. In the second step (post rumen), the digestibility of calsium soapproduction has dry matter digestibility of 74.85% and organic matter of digestibilty of 72.94%. Theresults could be concluded that in the rumen, calcium soap is the most microbial degradation resistantcompared the others and it can be degraded and digested in the abomasum to the small intestine.Therefore pH of rumen fluid is optimal, so it does not interfere with the fermentation in the rumen.Keywords: calsium soap, in vitro, dry matter digestibily, organic matter digestibility, pH value